Un análisis sintáctico, comparación de dos lenguas tipológicamente distintas: español y shipibo - Bozovich Bottger, Branko (2022)
We present a syntactic analysis of a language with an ergative-absolutive alignment, Shipibo, and a language with a nominative-accusative alignment. This is developed by deploying syntactic schemes in line with Marantz's case distribution hierarchy. Thus, transitive and intransitive utterances of each language have been assessed and compared, considering particular characteristics of each language. It has been noted that Spanish and Shipibo maintain a different case allocation amongst them. Likewise, it has been confirmed that the intransitive utterances of these languages do not exhibit greater differences than the transitive ones. Finally, it has not been possible to confirm whether constructions which share the same alignment could be equivalent between an accusative and an ergative language, given that the split-ergativity example studied in Shipibo maintains the ergative case.